History of the Taxonomic Studies of Marine Isopoda (Crustacea: Peracarida) from Argentina - Pereira, Emanuel (2023)
The order Isopoda is one of the most speciose and morphologically diverse order within the Crustacea worldwide, and the Southwest Atlantic is not the exception. The knowledge of the marine isopod fauna in the Argentine Continental Shelf and Slope spans almost two centuries. It began during the 19th century and the first half of the 20th century, when European and North American scientists directed their research to this part of world. Subsequently, some Argentine researchers continued the taxonomic studies on the Isopoda, focused mainly on intertidal and shallow waters species of the continental shelf. Currently, the taxonomic knowledge of Isopoda has significantly expanded due to the access to deep-sea environments. In the present contribution, the history of the taxonomic studies of Isopoda from Argentina is reviewed.